Impaired Malate and Fumarate Accumulation Due to the Mutation of the Tonoplast Dicarboxylate Transporter Has Little Effects on Stomatal Behavior. Issue 3 (12th September 2017) - Medeiros, David B.; Barros, Kallyne A.; Barros, Jessica Aline S.; Omena-Garcia, Rebeca P.; Arrivault, Stéphanie; Sanglard, Lílian M.V.P.; Detmann, Kelly C.; Silva, Willian Batista; Daloso, Danilo M.; DaMatta, Fábio M.; Nunes-Nesi, Adriano; Fernie, Alisdair R.; et al.
Abstract : Manipulation of tonoplastic organic acid transport by inhibition of the tDT impacts mitochondrion metabolism, while the overall stomatal and photosynthetic performance is not affected. Abstract: Malate is a central metabolite involved in a multiplicity of plant metabolic pathways, being associated with mitochondrial metabolism and playing significant roles in stomatal movements. Vacuolar malate transport has been characterized at the molecular level and is performed by at least one carrier protein and two channels in Arabidopsis ( Arabidopsis thaliana ) vacuoles. The absence of the Arabidopsis tonoplast Dicarboxylate Transporter (tDT) in the tdt knockout mutant was associated previously with an impaired accumulation of malate and fumarate in leaves. Here, we investigated the consequences of this lower accumulation on stomatal behavior and photosynthetic capacity as well as its putative metabolic impacts. Neither the stomatal conductance nor the kinetic responses to dark, light, or high CO2 were highly affected in tdt plants. In addition, we did not observe any impact on stomatal aperture following incubation with abscisic acid, malate, or citrate. Furthermore, an effect on photosynthetic capacity was not observed in the mutant lines. However, leaf mitochondrial metabolism was affected in the tdt plants. Levels of the intermediates of the tricarboxylic acid cycle were altered, and increases in both light and dark respiration were observed. We conclude that manipulation of the tonoplastic organic acid transporter impacted mitochondrial metabolism, while the overall stomatal and photosynthetic capacity were unaffected.